Electrical installation work - Scaddan, Brian (Newnes, 2008)
This well-known textbook is written for all electrical trainees who want to understand not only how, but why electrical installations are designed, installed and tested in particular ways. Brian Scaddan's approach encourages independent learning with end fo chapter self-assessment questions provided. The material is arranged into logical topic sections rather than following a particular syllabus. This makes the book a handy reference even after the course. However, the book meets the requirements of both Level 2 and 3 of the City & Guilds 2330 Certificate and the Level 3 2356 NVQ and a mapping grid to the learning outcomes is included. The new edition is fully in line with the 17th IEE Edition Wiring Regulations. In addition, the new full colur page design will help make learning easier for students of all abilities. Brian Scaddan , I Eng, MIET, is a consultant for and Honorary Member of City & Guilds. He has over 35 years' experience in Further Education and training. He is Director of Brian Scaddan Associates Ltd, an approved City & Guilds and NICEIC training centre offering courses on all aspects of Electrical Installation Contracting including the C&G 2382, 2391, 2392, 2377 series and NICEIC DISQ courses. He is also a leading author of books on electrical installation. * Fully up-to-date with the 17th Edition IEE Wiring Regulations * Tried and trusted content now with improved page design and in full colour * Covers both Level 2 and 3 in one volume
Includes index.
Keywords: Electric wiring, Interior.; Electric apparatus and appliances -- Installation.; elektronické knihy; electronic books